Conjugated Oligoelectrolytes: A Chain‐Elongated Oligophenylenevinylene Electrolyte Increases Microbial Membrane Stability (Adv. Mater. 18/2019). Issue 18 (2nd May 2019) - Zhou, Cheng; Chia, Geraldine W. N.; Ho, James C. S.; Moreland, Alex S.; Seviour, Thomas; Liedberg, Bo; Parikh, Atul N.; Kjelleberg, Staffan; Hinks, Jamie; Bazan, Guillermo C.
Abstract : Achieving biotechnological strain improvement using synthetic materials represents a simple approach compared to genetic techniques. In article1808021, Jamie Hinks, Guillermo C. Bazan, and co‐workers demonstrate a novel membrane‐intercalating phenylenevinylene oligoelectrolyte, S6. S6 treatment of Escherichia coli improves butanol tolerance two‐fold. Biophysical experiments deploying giant unilamellar vesicles show that S6 counters membrane instability caused by butanol exposure.